Substituted aromatic pentaphosphole ligands – a journey across the p-block. Issue 39 (14th September 2021) - Riesinger, Christoph; Balázs, Gábor; Seidl, Michael; Scheer, Manfred
Abstract : The reactivity of cationic electrophiles towards pentaphosphaferrocene [Cp*Fe(ƞ 5 -P5 )] is explored. We report P–E bond formation for electrophiles across the p-block, producing coordination complexes with unprecedented hetero-bispentaphosphole and hetero-pentaphosphole ligands. Abstract : The functionalization of pentaphosphaferrocene [Cp*Fe(η 5 -P5 )] (1 ) with cationic group 13–17 electrophiles is shown to be a general synthetic strategy towards P–E bond formation of unprecedented diversity. The products of these reactions are dinuclear [Cp*Fe2 μ, η 5:5 -(P5 )2 EX2 ][TEF] (EX2 = BBr2 (2 ), GaI2 (3 ), [TEF] − = [AlOC(CF3 )3 4 ] − ) or mononuclear [Cp*Fe(η 5 -P5 E)][X] (E = CH2 Ph (4 ), CHPh2 (5 ), SiHPh2 (6 ), AsCy2 (7 ), SePh (9 ), TeMes (10 ), Cl (11 ), Br (12 ), I (13 )) complexes of hetero-bis-pentaphosphole (( cyclo -P5 )2 R) or hetero-pentaphosphole ligands ( cyclo -P5 R), the aromatic all-phosphorus analogs of prototypical cyclopentadienes. Further, modifying the steric and electronic properties of the electrophile has a drastic impact on its reactivity and leads to the formation of [Cp*Fe(μ, η 5:2 -P5 )SbICp′′′][TEF] (8 ) which possesses a triple-decker-like structure. X-ray crystallographic characterization reveals the slightly twisted conformation of the cyclo -P5 R ligands in these compounds and multinuclear NMR spectroscopy confirms their integrity in solution. DFT calculations shed light on the bonding situation of these compounds and confirm the aromatic character of the pentaphosphole ligands on a journey across the p-block.